I Have to Give a Presentation, Now What?! - Westerfield, Jude (Recorded Books, Inc., 2017)
In this useful guide, Jude Westerfield gives tips on "overcoming your fears, using Powerpoint, and organizing your presentation." Have you ever gotten butterflies before speaking in public? Have you ever felt unprepared? With a few quick and easy steps, Westerfield will have you on your way to being a confident and organized speaker. Narrator Brian Keeler clearly voices each key point in this effective guidebook.